High-Density 3D Printable Chipless RFID Tag with Structure of Passive Slot Rings - Zhonghua Ma; Yanfeng Jiang (Sensors, 2019)
A three-dimensional (3D) printable chipless radio frequency identification (RFID) tag, with high density and sensitivity, is proposed and fulfilled on insulator substrates. By printing a rectangular slot ring and designing specific geometry on the substrate, the printed structure shows high sensitivity in a resonant manner, with the benefits of high density and low cost. Considering the multiple rectangular rings with different sizes in a concentric distribution, a bit coding sequence can be observed in frequency spectra because of the corresponding different resonant frequencies aroused by the printed slots. In this way, the 3D printable chipless RFID tag can be fulfilled by adopting the structure of the rectangular slot ring on the insulated substrates. The main characteristics of the designed rectangular slot rings are verified on both flexible and solid substrates. A 12-bit chipless tag based on the slot ring structures is designed and implemented. The simulation and experiment results show good agreement on its characteristics. The frequency response reveals the fact that the 2th, 3th and 4th harmonic do not exist, which is a unique merit for improving the encoding capacity and the sensitivity of the corresponding reader. The electric field direction of the electromagnetic wave of the reader excitation tag is demonstrated to be wide, up to 90° on the tag horizontal plane, 30° on the vertical direction.